Potential part of electric field of ICP coil - Azarenkov, N.A.; Gapon, A.V. (Вопросы атомной науки и техники, 2021)
ICP devices are widespread in modern technology, so the capacitive coupling in ICP is well known. It does not make a sufficient impact to the power deposition in plasma, and mostly it assumed to be a harmful effect [1]. Fortunately, making use of Faraday shield allows one to avoid a detail investigation of the capacitive coupling. However, in some cases it would be useful to account both coupling types of the inductor with a plasma [2]. There are many ways for analytical and numerical simulation of the inductors and their coupling with a plasma. In the most simulating tools, the problem comes to FEM PDE model, which includes as minima the body of an inductor wire and the surrounding space. In the paper, we use some other approach, based on integral solutions for electrodynamics potentials. Electric fields of some inductors are studied in the framework of the approach. Пристрої ICP дуже поширені в сучасній техніці, тому ємнісний зв’язок в ICP добре відомий. Він суттєво не впливає на введення енергії в плазму, і в більшості випадків вважається шкідливим ефектом [1]. Використання екрану Фарадея дозволяє уникнути докладного дослідження ємнісного зв’язку. Однак у деяких випадках корисно враховувати обидва типи зв’язку індуктора з плазмою [2]. Існує багато способів аналітичного і числового моделювання індукторів та їх зв’язку з плазмою. У більшості САПР проблема зводиться до розв’язку диференційних рівнянь методом скінченних елементів. У цій статті ми використовуємо інший підхід, заснований на інтегральних рівняннях для електродинамічних потенціалів. У рамках цього підходу досліджуються електричні поля різних індукторів. Устройства ICP широко распространены в современной технике, поэтому емкостная связь в ICP хорошо известна. Она не оказывает значительного влияния на ввод энергии в плазму, и в большинстве случаев считается вредным эффектом [1]. Использование экрана Фарадея позволяет избежать подробного исследования емкостной связи. Однако в некоторых случаях полезно учитывать оба типа связи индуктора с плазмой [2]. Существует множество способов аналитического и численного моделирований индукторов и их связи с плазмой. В большинстве САПР проблема сводится к решению дифференциальных уравнений методом конечных элементов. В этой статье мы используем другой подход, основанный на интегральных уравнениях для электродинамических потенциалов. В рамках этого подхода исследуются электрические поля различных индукторов.